Competition between fixed and mobile broadband access based on mobility and data volume - Julienne Liang (International Telecommunications Society (ITS), 2010)
This article proposes a duopoly model based on a model initially introduced by Shubik and Levitan to analyze the competition based on mobility and data volume between fixed and mobile broadband access. By the description of asymmetrical characteristics of fixed and mobile broadband offers and demand functions, Nash equilibrium can be derived through a game where both firms compete in price. This simple model is a first attempt in addressing the issue of partial fixed-mobile substitution. It allows modeling some effects of price interdependence between fixed and mobile markets and is used in a version of the "hypothetical monopolist" test (or SSNIP, Small but Significant and Nontransitory Increase in Price). The comparisons in terms of social welfare between fixed-mobile intermodal competition, fixed perfect competition and mobile perfect competition indicate that the fixed-mobile intermodal competition leads to a higher level of social welfare.
Keywords: 330